Improvement of Li-ion batteries energy storage by graphene additive. (February 2020) - AL-Saedi, Safaa I.; Haider, Adawiya J.; Naje, Asama N.; Bassil, Nathalie
Abstract: In this work, the layered compound of LiCo0.525 Ni0.475 O2, (LCNO) was prepared by self-propagating combustion reaction for the cathode of lithium-ion battery. We used self-propagating combustion reaction to prepare the compound of LiCo0.525 Ni0.475 O2, (LCNO) as a cathode material of lithium-ion battery, then we added Graphene (G) to LCNO as additive to obtain LCNO/G (LCNOG). Graphene weight is (4 %) of the total weight of LCNO, in a typical preparation, 10 g of LCNO, 0.4 g from G and 200 ml of ethanol were stirred together at room temperature to reach full dryness. We used thermo-gravimetric analysis (TGA) to determine the optimum range of annealing temperatures of LCNO and LCNOG. The value found were (650, 750 and 850) ∘ C for 12 h in air. Changes in the structural and morphological properties were also studied. The structural properties of LCNO and LCNOG powder were studied by means of X-ray diffraction (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), Energy Dispersive Spectrometry (EDS), Atomic Force Microscopy (AFM) and a Vibrating Sample Magnetometer (VSM). XRD analysis shows that all the powders are crystallized in the Space group R-3m, crystal system is trigonal (hexagonal axes) and present a random orientation and surface morphology of the LCNOG powder consists of Nano-crystalline grains with uniform coverage of the substrate surface with randomly oriented. XRD analysis showed that all the powders are crystallized in the Space group R-3m, crystal system is trigonal (hexagonal axes) and present a random orientation. Surface morphology of the LCNOG powder consists of Nano-crystalline grains with uniform coverage of the substrate surface with random orientation. Hysteresis behavior analysis proved that the powder possessed soft magnetic properties. Thermo-gravimetric analysis showed that the best annealing temperature and duration that leads to particles in the range several nm of the targeted composition are 750 °C for 12 h.